Persepsi Kemudahan, Kebermanfaatan dan Kepatuhan Wajib Pajak Terhadap Penggunaan E-filling - Imelda Sinaga; Victoria Ari Palma Akadiati; Agnes Susana Merry Purwanti (Penerbit Goodwood, 2022)
Purpose: of this study is to investigate the perception of convenience, the perception of usefulness, and taxpayer compliance with the use of e-filling in order to obtain variables that have a significant and insignificant effect. Method: uses primary data in the form of a questionnaire which is analyzed using multiple linear regression with a sample of teachers and employees of Yadika SMA/SMK Bandar Lampung. Results: showed that the perceived convenience variable had no significant effect, the perceived usefulness variable had a significant effect and, the taxpayer compliance variable has no significant effect on the use of e-filling. Limitations: of this study are that taxpayers still have difficulty in filling out e-filing, the use of